2011
DOI: 10.5897/ajb11.880
|View full text |Cite
|
Sign up to set email alerts
|

Impact of packaging material and storage time on olive oil quality

Abstract: Olive oil is very appreciated for its characteristic flavor and its biological and nutritional value which are strongly related to the quality. The effect of packaging materials (stainless, jar, clear polyethylenene terephthalate (PET), clear glass and dark glass bottles) on quality attributes of extra virgin olive oil (EVOO) was studied as a function of storage time (0 to 12 months). The results made it possible to highlight a light influence of time as well as type of container on the acidic composition of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Differences in sorption and migration between the 3 plastic packaging materials became significant at 3 months with PET showing significantly higher sorption than PLA (Table 8). Migration followed a similar pattern of increase as sorption for all 3 plastic materials ( [16] and EVOO [12] in contact with PET versus PLA. To the authors' knowledge, there is no published information related to migration/sorption when olive oil is in contact with PET versus HDPE or with HDPE versus PLA.…”
Section: Migration and Sorptionmentioning
confidence: 75%
See 2 more Smart Citations
“…Differences in sorption and migration between the 3 plastic packaging materials became significant at 3 months with PET showing significantly higher sorption than PLA (Table 8). Migration followed a similar pattern of increase as sorption for all 3 plastic materials ( [16] and EVOO [12] in contact with PET versus PLA. To the authors' knowledge, there is no published information related to migration/sorption when olive oil is in contact with PET versus HDPE or with HDPE versus PLA.…”
Section: Migration and Sorptionmentioning
confidence: 75%
“…In this study, the acidity of EVOO stored in clear glass without light exposure barely increased at the end of the 9-month storage period and remained below the established values for EVOO, however the PVs exceeded the upper standard limit of EVOO (20 meq O 2 /kg oil) ( Table 1 and Table 3). Peroxides are the main initial products resulting from lipid autoxidation during storage and serve as indicators of the degree of oxidative rancidity and quality change [12]. Although there is synergy between lipolysis (responsible for the increase in acidity) and lipid oxidation (responsible for the increase in PV), the latter can be accelerated by increased temperature, presence of water, and oxidative enzymes that are increased in case of fly spoilage [2].…”
Section: Changes In Physico-chemical Characteristics Of Evoomentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the introduction, several studies instrumentally assessed the impact of the packaging and storage time on the oil quality described by relevant indices (acidity, peroxide value, K232 and K270, total phenolic content). Traditional studies on oil storage suggested that oil stored in stainless steel had better qualitative level (with significantly higher levels of phenols and lower values of the oxidative indices) than that stored in transparent clear and green colored glass [16] and that stainless and dark glass appeared to be the most adequate packaging materials compared to clear PET or clear glass [42]. However, recent studies suggest other innovative packaging materials with outstanding oxygen barriers (e.g., flexible PET with UV-blocker) can outperform glass in terms of quality parameters [14], suggesting the need to further explore the impact of new innovative solutions.…”
Section: Effect Of the Storage Time And Packaging Materials On Acceptabilitymentioning
confidence: 99%
“…might change the quality characteristics of the olive oil products. For example‚ the high intensity of light in the store can accelerate the oxidation of oil (Dabbou, 2011). Similarly, the longer olive oil products remain in retail and unsold impacts on the acidity of the oil and the intensity of rancidity.…”
Section: Ccp8_ Risks Associated With Retail and Distributionmentioning
confidence: 99%